Leapfrogging: Time of entry and firm productivity - Josh Ederington; Georg Götz (Philipps-University Marburg, School of Business and Economics, 2018)
We develop a model in which ex ante identical firms make endogenous entry and technology adoption decisions. We show that this model is capable of matching the stylized facts in which entry and adoption are dispersed over time and that, in many industries, it is the newest firms which are the most likely to exhibit high productivity growth and adopt new innovations (i.e., leapfrogging). We then derive the characteristics of those industries where such leapfrogging is likely to occur and show that leapfrogging can induce reverse preemption (i.e., forward-looking incumbent firms delaying entry and adoption due to leapfrogging behavior). As an application, we demonstrate how, in an industry conducive to leapfrogging, research subsidies can actually reduce short-run consumer welfare by discouraging firms from entering the market with a basic technology.
Keywords: L11; 330; entry; technology adoption